Enhanced surveillance of tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis (Tdap) vaccines in pregnancy in the Vaccine Adverse Event Reporting System (VAERS), 2011–2015. Issue 20 (29th April 2016) - Moro, Pedro L.; Cragan, Janet; Tepper, Naomi; Zheteyeva, Yenlik; Museru, Oidda; Lewis, Paige; Broder, Karen
Abstract: Background: In October 2011, the Advisory Committee on Immunization Practices (ACIP) issued updated recommendations that all pregnant women routinely receive a dose of tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis (Tdap) vaccine. Objectives: We characterized reports to the Vaccine Adverse Event Reporting System (VAERS) in pregnant women who received Tdap after this updated recommendation (2011–2015) and compared the pattern of adverse events (AEs) with the period before the updated recommendation (2005–2010). Methods: We searched the VAERS database for reports of AEs in pregnant women who received Tdap vaccine after the routine recommendation (11/01/2011–6/30/2015) and compared it to published data before the routine Tdap recommendation (01/01/2005–06/30/2010). We conducted clinical review of reports and available medical records. The clinical pattern of reports in the post-recommendation period was compared with the pattern before the routine Tdap recommendation. Results: We found 392 reports of Tdap vaccination after the routine recommendation. One neonatal death but no maternal deaths were reported. No maternal or neonatal deaths were reported before the recommendation. We observed an increase in proportion of reports for stillbirths (1.5–2.8%) and injection site reactions/arm pain (4.5–11.9%) after the recommendation compared to the period before the routine recommendation for Tdap during pregnancy. We noted a decrease in reports of spontaneous abortion (16.7–1%). After the 2011 Tdap recommendation, in most reports, vaccination (79%) occurred during the third trimester compared to 4% before the 2011 Tdap recommendation. Twenty-six reports of repeat Tdap were received in VAERS; 13 did not report an AE. One medical facility accounted for 27% of all submitted reports. Conclusions: No new or unexpected vaccine AEs were noted among pregnant women who received Tdap after routine recommendations for maternal Tdap vaccination. Changes in reporting patterns would be expected, given the broader use of Tdap in pregnant women in the third trimester.